MEMBANGUN GUGATAN YANG SAH: ANALISIS PENGARUH KEJELASAN OBJEK DAN PEMENUHAN UNSUR-UNSUR GUGATAN DALAM PROSES LITIGASI DI PENGADILAN NEGERI TANGERANG - Gunawan Widjaja; Iriaty Khairul Ummah (The Juris, 2025)
A civil lawsuit serves as a formal legal instrument that must be systematically drafted in accordance with procedural and substantive requirements under Indonesian civil procedural law. This study aims to examine the essential elements of a valid lawsuit and to assess how the implementation of these requirements affects judicial decisions at the Tangerang District Court. The research employs a normative and empirical legal approach. Normative data were obtained through legal literature and statutory analysis, while empirical data were drawn from civil case decisions published in 2024 through the Case Tracking Information System (SIPP). The findings reveal that inconsistencies between the posita and petitum, along with unclear identification of the object of dispute, are the main reasons for lawsuits being declared inadmissible (niet ontvankelijk verklaard) or rejected. Out of 789 examined cases, 442 were granted, while 120 were dismissed as inadmissible and 16 were rejected. These outcomes reflect the significant impact of procedural compliance on case resolution and underscore the importance of technical precision in lawsuit drafting. The study affirms that drafting a coherent and complete lawsuit is not merely a procedural formality, but a vital component of legal accountability and access to justice. As such, strengthening the capacity of legal practitioners and law students in the formulation of civil lawsuits should be a key focus in legal education and professional development in Indonesia.